Emotional labor, teacher burnout, and turnover intention in high-school physical education teaching. (February 2019) - Lee, Ye Hoon
Grounded upon the conservation of resources theory, this study sought to examine the relationships between the three emotional labor strategies, teacher burnout, and turnover intention among physical education teachers. A total of 613 high-school physical education teachers from 47 states across the United States completed online questionnaires that measured the proposed variables. The goodness-of-fit statistics indicated that the structural model showed a reasonable fit, χ 2 (605) = 1391.26 = 2.30, p < 0.01; RMSEA = .05; TLI = .93; CFI = .93. The results also revealed that teacher burnout was positively associated with surface acting and negatively associated with genuine expression. Further, teacher burnout was positively associated with turnover intention. Mediation analysis showed that teacher burnout fully mediated the trajectory from emotional labor strategies to turnover intention. The results highlight the impact of emotional labor on physical education teachers' well-being and intention to leave the teaching profession.